1994
DOI: 10.1117/12.171928
|View full text |Cite
|
Sign up to set email alerts
|

Lossless compression of Peanoscanned images

Abstract: Peanoscanning was used to obtain the pixels from an image by following a scan path described by a space-filling curve, the Peano-Hilbert curve. The Peanoscanned data were then cornpressed without loss of information by direct Huffrnan, arithmetic, and Lernpel-Ziv-Welch coding, as well as predictive and transform coding. In our implementation, tested on seven natural images, Peano-differentialcoding with an entropy coder gave the best results of reversible compression from 8 bits/pixel to about 5 bits/pixel, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The Hilbert curve [42] is one of the well-recognized fractals that demonstrates this behavior. An important property of the Hilbert curve, also referred to as the Peano curve or the Peano-Hilbert curve [51], is that it visits all of the subsquares or their center points in a given quadrant or subquadrant of the given space before leaving the same for the next subquadrant. In contrast to this notion of dimension, Hilbert demonstrated that a curve can fill a 2D plane, that is, after an infinite number of iterations, the Hilbert curve will pass through every point in a plane without crossing itself.…”
Section: Famous Fractalsmentioning
confidence: 99%
“…The Hilbert curve [42] is one of the well-recognized fractals that demonstrates this behavior. An important property of the Hilbert curve, also referred to as the Peano curve or the Peano-Hilbert curve [51], is that it visits all of the subsquares or their center points in a given quadrant or subquadrant of the given space before leaving the same for the next subquadrant. In contrast to this notion of dimension, Hilbert demonstrated that a curve can fill a 2D plane, that is, after an infinite number of iterations, the Hilbert curve will pass through every point in a plane without crossing itself.…”
Section: Famous Fractalsmentioning
confidence: 99%
“…It is defined in the following way: (28) where is the mean-squared error between the luminance channel of the reconstructed and the original frames. In the case of TMN4, the PSNR frame distortion can be written as (29) since the region distortion only depends on the selected motion vector and the selected quantizer for that region. We use "quarter common intermediate format" (QCIF) sequences, which have dimensions 176 144 pixels.…”
Section: A Video Compression Scheme With Optimal Bit Allocation Bementioning
confidence: 99%
“…Hilbert curves have been used in image and video processing as scanning paths on the pixel level in the luminance domain for lossless coding [29] and lossy coding [30]. They have also been used as a scanning path for the coefficients in the transform domain [31].…”
Section: A Video Compression Scheme With Optimal Bit Allocation Bementioning
confidence: 99%
“…For all images they investigated, Abdollahi et al achieved the lowest entropy-ratios when the Hilbert Curve was applied. Provine and Rangayyan compress greyscale images mapped with the Hilbert and Raster Curves using HFF, Arithmetic Coding, Predictive Coding, and LZW [35]. The highest compression ratios they achieve, of approximately R c = 5, are obtained with HFF combined with differential coding, a form of predictive coding.…”
Section: Introductionmentioning
confidence: 99%